2006
DOI: 10.1007/s11274-006-9229-y
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of enhanced aeration using perfluorodecalin in Yarrowia lipolytica cultures for lipase production

Abstract: The inadequate supply of oxygen to biomass is a critical factor to the productivity of most aerobic submerged fermentations. This happens because oxygen is sparingly soluble in the aqueous media. The use of a second liquid phase of perfluorocarbon (PFC), an oxygen-carrying compound, in the culture medium can increase the availability of oxygen to the microorganisms. The effect of perfluorodecalin on Yarrowia lipolytica cultures was investigated in shake-flask cultures. It was found that the specific growth rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Due to the high oxygen mass transfer rate, the cells had more oxygen in the medium giving higher growth rates, and less time is necessary to obtain maximum cell concentration. The improvement of specific cellular growth of Y. lipolytica by OTR enhancement trough other means than pressure was previously observed, as is the case of oxygen carrier use, like perfluorocarbons [19].…”
Section: Air Effects On Cell Growthsupporting
confidence: 61%
See 1 more Smart Citation
“…Due to the high oxygen mass transfer rate, the cells had more oxygen in the medium giving higher growth rates, and less time is necessary to obtain maximum cell concentration. The improvement of specific cellular growth of Y. lipolytica by OTR enhancement trough other means than pressure was previously observed, as is the case of oxygen carrier use, like perfluorocarbons [19].…”
Section: Air Effects On Cell Growthsupporting
confidence: 61%
“…Y. lipolytica W29 adapts rapidly to hyperbaric conditions; thus, these conditions can be imposed to cultures of this strain as a way of preventing oxygen limitation to cell growth and as a mean of enzyme production improvement such as lipases and SOD. Air pressure can be seen as an important operating parameter such as medium composition [19] and strain selection [23] for lipase production optimisation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, lipase production by Y. lipolytica IMUFRJ 50 682 was favoured at high oxygen availability, as demonstrated in experiments with perfluorocarbons. 38,39 Also, lipase activity in cultures of Y. lipolytica W29 (ATCC 20 460) was increased at improved oxygenation in pressurised bioreactors. 40 Once again, the diverse behaviour of different strains is stressed.…”
Section: Batch Enzyme Production In Bench-scale Bioreactorsmentioning
confidence: 99%
“…Preliminary shake-flask experiments showed that the use of perfluorodecalin as an oxygen carrier in the fermentation medium increased lipase production from Yarrowia lipolytica (Amaral et al, 2006a(Amaral et al, , 2007. Frost and Moss (1987) results indicate that improvements in aeration by agitation or air sparging are beneficial to lipase production by single cell organisms and filamentous moulds.…”
Section: Introductionmentioning
confidence: 99%